The Potential Role of Quercus Infectoria Gall Extract on Osteoblast Function and Bone Metabolism - Hapidin, Hermizi; Abdullah, Hasmah; Soelaiman, Ima Nirwana (2012)
The galls of the Quercus infectoria (QI) tree are traditionally believed to have great medicinal value. Pharmacologically the galls are claimed to have various biological activities such as astringent effect, antidiabetic, antitremorine, local anaesthetic, antipyretic, anti-inflammatory, antibacterial, antiviral and many more. These pharmacological activities of gall extracts were reported to be due to its excellent antioxidant activity with phytochemicals constituents of phenolic and flavanoid compounds. The phenolic compounds or polyphenols can act on bone metabolism by modulating os-teoblast proliferation, differentiation and mineralization, as well as osteoclastogenesis. In addition, elemental and phys-ico-chemical analysis indicated the presence of important minerals in QI, such as calcium, magnesium, phosphorus, oxygen, potassium, aluminium, carbon, zinc, iron, manganese, nickel and silica. The current review will be focusing on the potential bone health benefits of the well-known traditional herbal medicine, QI or locally known as the “manja-kani”.